Floral Resources Used by Euglossini Bees (Hymenoptera: Apidae) in Coastal Ecosystems of the Atlantic Forest - L. C. Rocha-Filho; C. Krug; C. I. Silva; C. A. Garófalo (Psyche: A Journal of Entomology)
In spite of playing an important ecological role as pollinators of tropical ecosystems, orchid bees are still poorly known regarding their floral resources. Aiming at a better comprehension of the importance of different plants visited by the Euglossini and, consequently, their role in the maintenance and reproduction of plant species in tropical ecosystems, this study aimed at identifying the flowers visited by those bees in two different areas of the Atlantic Forest in the northern coast of the state of São Paulo, Brazil. Sampling was carried out from August 2007 to July 2009 in two coastal ecosystems in Ubatuba, Brazil. In order to obtain information on flower resources collected by Euglossini bees in loco, all bees observed on flowers were collected, pollinaria of Orchidaceae occasionally attached to the body of males were identified, and the pollinic analysis of 68 females was carried out. One hundred twelve bees from 14 species were associated to 105 plant species which represented pollen, nectar, resin, and fragrances sources. These data reinforce the relevance of orchid bees to the maintenance and reproductive success of many tropical plants.